A reação de Diels-Alder de para-benzoquinonas sob condições de catálise por ácidos de Lewis e sob efeito de micro-ondas - Donatoni, Maria Carolina (2013)
In this work it was done the studies of the Diels-Alder reactions of the parabenzoquinones 2,5-dimethyl-para-benzoquinone (A1), 2,6-dimethyl-parabenzoquinone (A2) and thymoquinone (A3) with the dienes cyclopentadiene (B1), 2,3- dimethyl-1,3-butadiene (B2), isoprene (B3), trans-piperylene (B4) and 1- vinylcyclohexene (B5) (Figure I) under catalysis conditions employing as catalyst a mixture of Aerosil® silica and iron chloride (III). The amount of silica used was equimolar with respect to para-benzoquinones, and the iron chloride was employed in catalytic amounts of 4 mol% and 10 mol%. Under these catalysis conditions it was observed the reduction of the reaction times and a significant increase in yield for all the Diels-Alder reactions studied when compared to results obtained when the same reactions were carried out at room temperature and absence of catalysis. In the case of the Diels-Alder reaction of 2,6-dimethyl-para-benzoquinone (A2) with unsymmetrical dienes isoprene (B3), trans-piperylene (B4) and 1-vinylcyclohexene (B5), under catalytic conditions it was observed the reversal of the regioselectivity of these reactions when compared to the regioselectivities obtained for these reactions performed in the absence of catalysis... (continue)